Constitutive secretory expression and characterization of nitrilase from Alcaligenes faecalis in Pichia pastoris for production of R‐mandelic acid. (18th March 2021) - Zhang, Xinhong; Wang, Chuyan; Ge, Yang; Meng, Qingnan; Zhang, Yi
ABSTRACT: Nitrilases can directly hydrolyze nitrile compounds into carboxylic acids and ammonium. To solve the current problems of bioconversions using nitrilases, including the difficult separation of products from the resting cells used as the catalyst and high costs of chemical inducers, a nitrilase from Alcaligenes faecalis was heterologously expressed in Pichia pastoris X33. The stable nitrilase‐expressing strain No.39‐6‐4 was obtained after three rounds of screening based on a combined detection method including dot‐blot, SDS‐PAGE, and western blot analyses, which confirmed the presence of recombinant nitrilase with a molecular mass of about 50 kDa. The temperature and pH optima of the nitrilase were 45°C and pH 7.5, respectively. Cu 2+, Zn 2+, and Tween 80 strongly inhibited the enzyme activity, but the optical purity of the product R ‐mandelic acid ( R ‐MA) was stable, with practically 100% enantiomeric excess ( ee ). The nitrilase‐producing P. pastoris strain developed in this study provides a basis for further research on the enzyme. Abstract : Graphical Abstract: